2011
DOI: 10.1074/jbc.r110.191429
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of α2,6-Sialic Acid as a Negative Regulator of Galectin Binding and Function

Abstract: Galectins are ␤-galactoside-binding lectins that regulate diverse cell behaviors, including adhesion, migration, proliferation, and apoptosis. Galectins can be expressed both intracellularly and extracellularly, and extracellular galectins mediate their effects by associating with cell-surface oligosaccharides. Despite intensive current interest in galectins, strikingly few studies have focused on a key enzyme that acts to inhibit galectin signaling, namely ␤-galactoside ␣2,6-sialyltransferase (ST6Gal-I). ST6G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
124
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 96 publications
10
124
0
2
Order By: Relevance
“…This sialylation-dependent survival benefit is likely mediated through multiple molecular pathways. Studies by our group and others have shown that ST6Gal-I-directed ␣2-6 sialylation of selected receptors serves as a key negative regulator of galectin-induced apoptosis (39,42,43). Additionally, the diminished internalization of PECAM due to ␣2-6 sialylation allows anti-apoptotic signaling from PECAM for a longer time interval (40).…”
Section: Discussionmentioning
confidence: 99%
“…This sialylation-dependent survival benefit is likely mediated through multiple molecular pathways. Studies by our group and others have shown that ST6Gal-I-directed ␣2-6 sialylation of selected receptors serves as a key negative regulator of galectin-induced apoptosis (39,42,43). Additionally, the diminished internalization of PECAM due to ␣2-6 sialylation allows anti-apoptotic signaling from PECAM for a longer time interval (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, GM3, the ganglioside containing the sialyllactose epitope, has been reported to interact with EGFR and inhibit its kinase activity in a model supplemented with the GM3 glycolipid, and treatment with neuraminidase can rescue the autophosphorylation of EGFR (37). In addition, galectin-3 also can regulate the cellular trafficking and the level of surface EGFR through binding to the glycans on EGFR, and the binding can be blocked by sialylation on EGFR (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GnT-V in either HepG2 parent cells or its ST6GAL1 knock-out cells promoted the cell migration, although GnT-V-overexpressing cells exhibited higher metastatic ability than the GnT-V-overexpressing ST6GAL1 knock-out cells (data not shown). Further, it has been shown that GnT-V plays a pro-metastatic role, at least partially, via interacting with galectin-3 (62), whereas the ␣2,6-sialylation but not ␣2,3-sialylation of N-glycan is able to inhibit its binding to galectin-3 (60,63). Therefore, it is reasonable to consider that ST6GAL1 and GnT-V contributes to the malignant progression by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%